2013
DOI: 10.1111/jep.12063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a national evidence‐based health care course via teleconference in a developing country

Abstract: The Brazilian EBH course via teleconference improved the knowledge and skills of public-sector health professionals and was approved by the vast majority of students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(41 reference statements)
0
4
0
1
Order By: Relevance
“…Yolsal et al [4] reported that 163 Turkish residents from different programs had a significant increase in test scores at the end of a three-day (17 h) presencial course about reproductive and sexual health and that the residents felt more prepared, motivated and confident to manage sexual issues with their patients. Similarly, other studies [21,25] reported significant increases in participants' knowledge on other health topics upon completion of online courses.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Yolsal et al [4] reported that 163 Turkish residents from different programs had a significant increase in test scores at the end of a three-day (17 h) presencial course about reproductive and sexual health and that the residents felt more prepared, motivated and confident to manage sexual issues with their patients. Similarly, other studies [21,25] reported significant increases in participants' knowledge on other health topics upon completion of online courses.…”
Section: Discussionmentioning
confidence: 57%
“…The majority of the 219 Ob/Gyn residents who participated in this study had little or no previous training about sexuality in medical school or in their residency program, yet the number of dropouts after enrollment was high (34.7%). This is a common finding in online courses in health sciences and may be related to difficulties in organizing their time and having the necessary self-discipline to participate in this type of activity [21].…”
Section: Discussionmentioning
confidence: 99%
“…LMICs may have limited physical and financial resources, including educational and clinical facilities and the necessary staff to manage them (Kim et al 2015;Ma et al 2020). The sheer number of staff requiring CPE to improve their skills and practice standards may place further strains on existing services (Macedo et al 2013;Puchalski Ritchie et al 2016) and educational approaches developed by well-meaning HICs may fail to take account of local circumstances. For example, several international programmes are only offered in English, or by distance learning, excluding those who lack the necessary language skills, technology, or reliable sources of electricity (Kim et al 2015;Puchalski Ritchie et al 2016).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Between 2005 and 2016, a year-long distance learning course (300 hours) on EBM for healthcare professionals had been conducted. By 2009, there were approximately 3,500 professionals regularly attending the course [4].…”
Section: Distance Learning Coursesmentioning
confidence: 99%